Gene machine : the race to decipher the secrets of the ribosome - Ramakrishnan, Venki, 1952- (Basic Books, 2018)
Everyone has heard of DNA. But by itself, DNA is just an inert blueprint for life. It is the ribosome--an enormous molecular machine made up of a million atoms--that makes DNA come to life, turning our genetic code into proteins and therefore into us. Gene Machine is an insider account of the race for the structure of the ribosome, a fundamental discovery that both advances our knowledge of all life and could lead to the development of better antibiotics against life-threatening diseases. But this is also a human story of Ramakrishnan's unlikely journey, from his first fumbling experiments in a biology lab to being the dark horse in a fierce competition with some of the world's best scientists. In the end, Gene Machine is a frank insider's account of the pursuit of high-stakes science.